Determination of the essential effect of modification in the composition of the combined vibration treatment technology on the mechanical properties of AK7 alloy - Selivorstov, Vadim; Dotsenko, Nataliia; Dotsenko, Yuri; Dotsenko, Vadym (Technology audit and production reserves, 2018)
The object of research is AK7 alloy, which is subjected to the complex action of vibration and modification in the process of producing cylindrical billets by means of casting in a metal mold. One of the most problematic places is the determination of rational modes of influence of technological factors on the alloy, ensuring the satisfaction of a given level of properties in terms of their competitive nature. During the study, the methods of regression analysis were used and identified as promising methods of analysis of variance to improve the accuracy of the findings. In particular, the results of the regression analysis of experimental and industrial research data on the vibration treatment technology with a frequency of 100–150 Hz with an additional input of the ultradisperse modifier into the melt are presented. The results are obtained concerning the confirmation of the hypothesis about the significance of the influence of the modifier on the increase of the mechanical properties of the alloy: НВ, σ0.2, σs, δs, ψ. This is important because attempts to improve the properties of the alloy using the combined technological solutions invariably cause the expenditure of energy and material resources. This ensures the possibility of energy and resource savings in the process. The obtained results show that the use of modification as an additional component of the technological process increases only ψ, but reduces HB and δs. In the vibration frequency range of 100–140 Hz, modification has a positive effect on σ0.2, and an increase in the frequency above this value leads to a deterioration in the result. The opposite effect is observed with respect to δs – with an increase in the vibration frequency of more than 140 Hz, modifying increases this alloy characteristic, in the range of 100–140 Hz, the introduction of a modifier can be considered justified. Thus, it is found that the modification has an ambiguous effect on the properties of the alloy, therefore, in order to select a rational technological regime, a solution to the compromise problem is necessary. This is due to the revealed fact of competing properties. It is proposed to use the methods of analysis of variance to refine the obtained results.